VERTICAL DISTRIBUTION OF DISSOLVED ORGANIC CARBON IN THE NORTH PACIFIC AS DETERMINED BY THE HIGH-TEMPERATURE CATALYTIC OXIDATION METHOD - Tanoue E. (My University, 1992)
Three vertical profiles of dissolved organic carbon (DOC) in the North Pacific, as determined by the high-temperature catalytic oxidation (HTCO) method, are reported, together with the results of some analytical studies. A comparison of calibrations of the DOC analyzer, using as standards two types of organic compound and an inorganic compound, revealed that recoveries of standard organic compounds were below 100%, an indication that the recovery of DOC in seawater is also likely to be less than 100%. It is also suggested that a running system blank (instrument blank plus sample memory blank) should be estimated during accurate measurement of DOC. The concentrations of DOC in the upper 200 m and below 500 m were 148 +/- 19 (n = 12) and 113 +/- 8 (n = 11) muM C at the station at 25°N, and 87.7 +/- 5.2 (n = 11) and 78.2 +/- 7.1 (n = 11) muM C at the station at 45°N. The average concentrations in the present study are 1.3 times higher at the surface and 1.8 times higher in the intermediate and deep water layers than those measured by the wet oxidation method at other site in the northern North Pacific. The concentrations and vertical characteristics of DOC in the present study were quite different from those reported previously using the HTCO method in the western North Pacific. Profiles of the concentration of DOC showed no clear correlation with those of dissolved oxygen. Thus, the correlation between DOC and apparent oxygen utilization (AOU) was very weak or statistically insignificant in the intermediate and deep waters.